2021
DOI: 10.1186/s12870-021-02857-2
|View full text |Cite
|
Sign up to set email alerts
|

Linkage analysis, GWAS, transcriptome analysis to identify candidate genes for rice seedlings in response to high temperature stress

Abstract: Background Rice plants suffer from the rising temperature which is becoming more and more prominent. Mining heat-resistant genes and applying them to rice breeding is a feasible and effective way to solve the problem. Result Three main biomass traits, including shoot length, dry weight, and fresh weight, changed after abnormally high-temperature treatment in the rice seedling stage of a recombinant inbred lines and the natural indica germplasm popu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 43 publications
0
22
0
1
Order By: Relevance
“…Increasing evidence has revealed that N supply has a significant impact on plant growth and development (McAllister et al, 2012;Chen et al, 2016). However, the conventional approach of linkage mapping has been used to identify potential genes with phenotypic variation, and even when this approach was limited to a biparental experimental population, it was timeconsuming Wei et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence has revealed that N supply has a significant impact on plant growth and development (McAllister et al, 2012;Chen et al, 2016). However, the conventional approach of linkage mapping has been used to identify potential genes with phenotypic variation, and even when this approach was limited to a biparental experimental population, it was timeconsuming Wei et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…This step was performed mainly because of the absence of available data for several neglected species in public databases (Schaefer et al, 2018), such as H. brasiliensis. Moreover, transcriptome assemblies are a way of categorizing a broader range of important genes found under stress conditions (Valdés et al, 2013;Wei et al, 2021), as already reported by other Hevea studies (Ahn et al, 2017;Mantello et al, 2019). Additionally, because of the recent availability of the Hevea genome (Liu et al, 2020a), more studies are required for complete and accurate gene categorization.…”
Section: Genome-wide Association Studiesmentioning
confidence: 84%
“…Over the past decade, the loci underlying tens of rice traits were identified by GWAS, and several important genes were successfully verified by further transgenic experiments (Wang et al, 2020;Chen et al, 2022a). For heat tolerance, Wei et al identified 77 loci associated with survival rate after heat treatment at the seedling stage by GWAS based on a panel of 255 rice accessions and identified LOC_Os02g12890 as an important candidate gene that may respond to high-temperature stress based on integrated transcriptome analysis (Wei et al, 2021). In addition, Yang et al detected ten heat-associated QTL by GWAS with 221 rice accessions and selected 11 promising candidate genes by combining GWAS and transcriptome data (Yang et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…For heat tolerance, Wei et al. identified 77 loci associated with survival rate after heat treatment at the seedling stage by GWAS based on a panel of 255 rice accessions and identified LOC_Os02g12890 as an important candidate gene that may respond to high-temperature stress based on integrated transcriptome analysis ( Wei et al., 2021 ). In addition, Yang et al.…”
Section: Introductionmentioning
confidence: 99%